Current concepts in SARS treatment - Fujii, Takeshi (J Infect Chemother, 2004)
The outbreak of severe acute respiratory syndrome (SARS) has drawn enormous attention and caused fear worldwide since early 2003. The disease appears to be under control now; however, the possible return of SARS must be emphasized. Although many clinical experiments have been reported, the treatment of SARS is largely anecdotal, and so far no treatment consensus has been reached. We summarize 14 clinical reports and attempt to assess the effectiveness of various treatment regimens. A combination treatment of steroids and ribavirin was widely used empirically from the outset of the epidemic. In general, the use of steroids for SARS seemed beneficial, but the optimal timing, dosage, and duration of treatment have not yet been determined. On the other hand, ribavirin administration apparently reduced neither the rate of intratracheal intubation nor that of mortality. Moreover, significant toxicity, such as hemolytic anemia, has been attributed to ribavirin. A few preliminary trials and in vitro data suggest the possibility of treating SARS with interferon. Other agents, including the HIV protease inhibitor glycyrrhizin and convalescent plasma, remain to be evaluated.